Selectivity in the Intermolecular Diels–Alder Reaction of Conjugated Trienes: Experimental and Theoretical Approaches. Issue 42 (21st August 2018) - Remeur, Camille; Desrat, Sandy; Gandon, Vincent; Roussi, Fanny
Abstract : Eleven analogs of the natural product meiogynin A, an inhibitor of proteins of the Bcl‐2 family, have been elaborated by an intermolecular Diels–Alder (DA) reaction of various conjugated chloro‐trienes, in order to determine the influence of the modification of the south part of meiogynin A on its biological activity. The chloro‐trienes were obtained in two to five steps from commercial compounds through a selective hydrochlorination of bromoalkyne intermediates to ( Z )‐1, 2‐dihalogenated alkenes followed by a chemoselective Suzuki–Miyaura cross‐coupling. The intermolecular DA reaction of these trienes with two α, β‐unsaturated carboxylic acids as dienophiles occurred with a perfect regioselectivity and good to excellent diastereoselectivities. These selectivities could be rationalized by DFT calculations. Abstract : Eleven analogs of the natural product meiogynin A, an inhibitor of proteins of the Bcl‐2 family, have been elaborated by an intermolecular Diels–Alder (DA) reaction of various conjugated chloro‐trienes with two α, β‐unsaturated carboxylic acids as dienophiles. The perfect regioselectivity and good to excellent diastereoselectivities of these reactions were rationalized by DFT calculations.